Hubungan Pendapatan dan Sikap Masyarakat Muslim Kecamatan Semampir Surabaya dengan Minat Membayar Wakaf Uang - Anwar, Moch. Khoirul; Khoirun (Jurnal Ekonomika dan Bisnis Islam, 2019)
The purpose of this study was to analyze the correlation of income and attitudes of the Muslim society in Semampir District Surabaya with interest in paying cash waqf. The independent variable in this study consisted of 2 variables, namely income variables and attitude variables. Income variables are measured using indicators of the amount of wages, other income and household expenses. While attitude variables are measured using cognitive, affective and conative component indicators. The dependent variable in this study is interest and measured using indicators of awareness, choice, attention and desire. This research method uses a quantitative approach with Kendall's correlation analysis and multiple correlation. The sample in this study amounted to 100 respondents using accidental sampling technique. The results of this study indicate that income has a low and significant correlation with interest in paying cash waqf with a value of 0.200. Whereas the attitude has a moderate and significant correlation with the interest in paying cash waqf with a value of 0.404. And there is a moderate and significant correlation between income and attitudes of the Muslim society in Semampir District Surabaya with an interest in paying cash waqf with a value of 0.573.